2008
DOI: 10.1210/jc.2006-2300
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Levels in a Population with No Clinical, Autoantibody, or Ultrasonographic Evidence of Thyroid Disease: Implications for the Diagnosis of Subclinical Hypothyroidism

Abstract: These results indicate that the TSH reference range should be narrowed and support a value of approximately 4.0 as the upper-reference limit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
4
10

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 24 publications
10
76
4
10
Order By: Relevance
“…Despite the fact that examination of individuals was not based on NACB guidelines, which was not published when data were collected for our study, our interval limits can be assumed to be correct for middle-aged French adults. In fact, we found an upper limit of ;4.0 mU/L; this value is close to the upper limit determined in studies using NACB guidelines (11,14,24,26,(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the fact that examination of individuals was not based on NACB guidelines, which was not published when data were collected for our study, our interval limits can be assumed to be correct for middle-aged French adults. In fact, we found an upper limit of ;4.0 mU/L; this value is close to the upper limit determined in studies using NACB guidelines (11,14,24,26,(32)(33)(34)(35).…”
Section: Discussionsupporting
confidence: 89%
“…In fact, autoimmune thyroid disease is very common in this population (37), and individuals assumed to be disease free may have been contaminated by earlier occult autoimmune thyroid disease not detected by ultrasonography. However, several recent studies of thyroid-disease-free individuals found no significant change in the TSH upper limit in patients with antithyroid antibodies (14,35,38). In addition, thyroid hypoechogenicity, a criterion used in our study, is considered a reliable tool for identifying chronic autoimmune disease (39).…”
Section: Discussionmentioning
confidence: 49%
“…The mean serum TSH in our patients with benign disease was 1.01 mIU=L. This is lower than the mean or median serum TSH values reported in large studies of the United States population (29)(30)(31). For example, the mean TSH in those individuals without any thyroid abnormalities was 1.48 mIU=L in the recent study by Hamilton and coworkers (31).…”
Section: Jonklaas Et Alcontrasting
confidence: 77%
“…Limitations in this approach include analytical issues, genetic variability, uncertainty about the reference range, high ratio of the basic intra-individual to inter-individual variability and considerable natural intra-individual fluctuations (10,11,12,13,21,22,23,24,25,26,27,28,29). A lack of correlation with clinical symptom scores occurs particularly in patients with subclinical hypothyroidism (30).…”
Section: Discussionmentioning
confidence: 99%